Spontaneous Coronary Artery Dissection in the Postoperative Period: A Case Report. Issue 3 (1st August 2019) - Bendinelli, Valentina; Lefebvre, Pascal; Daper, Anne
Abstract : Spontaneous coronary artery disease is an uncommon and likely underdiagnosed cause of sudden cardiac death affecting typically young and middle-aged women. We report a case of spontaneous coronary artery disease in the postoperative period in a female patient who developed an acute coronary event after gynecologic surgery. The patient was clinically asymptomatic except for mild hemodynamic instability and ST-segment–elevation myocardial infarction seen on electrocardiogram. Spontaneous coronary artery disease was diagnosed with coronary angiography, and a pharmacological therapy was instituted with favorable results.